Efficient quantum random number generation via simultaneously detecting photons in temporal and spatial dimensions - Bingkun Wang; Jianyong Hu; Xingjian Li; Jianqiang Liu; Shuxiao Wu; Haizhen Li; Liwen Zhang; Changgang Yang; Zhixing Qiao; Ruiyun Chen; Guofeng Zhang; Chengbing Qin; et al. (Scientific Reports)
Abstract Quantum random number generators (QRNGs) produce true random numbers with significant applications in quantum communication and numerical computation, where high-rate random number generation is critical. Photon detection-based quantum random-number generation methods have been widely studied. However, the generation rate is constrained by the count rate of single-photon detectors. This study proposes an efficient method that enhances random number generation by simultaneously detecting photons in temporal and spatial dimensions. We achieved simultaneous detection of photon arrival time and spatial position by employing a laboratory-developed 5 × 5 single-photon detector array and a high-saturation count rate multichannel time-to-digital converter. The maximum efficiency of the method was 21.1 bits per event and it maintained a consistent efficiency of 17.6 bits per event while achieving a random number generation rate of 2.1 Gbps. The proposed QRNG approach offers a promising pathway for significantly increasing random number generation rates, benefiting applications that require secure and high-speed random number sequences.